Penggambaran Laki-Laki Sebagai Korban Kekerasan Seksual dalam Pemberitaan di Media Online - Vina Karlameta Suhandi (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
This research aims to see how men as victims of sexual violence are portrayed in the news. The depiction of men as victims of sexual violence is seen using the Theo Van Leeuwen model of critical discourse analysis and a gender perspective. This research uses a descriptive type qualitative approach with documentation data collection methods. The results of the research show that in the reporting carried out by the five online media with the highest percentage level of public trust, there were only 22 stories that discussed men as victims of sexual violence during the period January – December 2023. The process of depicting men as victims of sexual violence was also not found exclusion. In this research, discourse was found based on cases of sexual violence, which were categorized based on strategies in the inclusion process that depicted men as victims of sexual violence. The depiction of men as victims of sexual violence is based on the strategies found, there is an imbalance between the position of the perpetrator and men as victims of sexual violence in the reporting carried out by the five media. The media depicts revictimization or victimization over and over again.